(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
The apple blister mite, Eriophyes mali Nalepa, 1926 (Acari: Prostigmata: Eriophyoidea), has been recently found in Serbia as a new pest of apple. The history of its research, the results of a morphological analysis and degree of infestation are presented. A comparison of the main morphological features of mites from different populations of remote geographical origin has shown that the apple blister mite from Serbia is most similar to another European population (Bulgarian [or Austrian?]) while it differs from E. mali originating from the USA and New Zealand. The percentage of infestation varied from 1.6% to 87.6%, with an average of 22.4%.